Merchants of legalism : a history of state responsibility (1870-1960) - Nissel, Alan T. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2024)
"This engaging study examines the duality of state responsibility for violations of international law and provides the first in-depth, extensive history of this modern doctrine. Will enrich researchers, practitioners and students interested in diplomacy, international law, legal history and the regulation of international enforcement actions"--
The responsibilities of states in international law : an overview -- The U.S. turn to the technique of international arbitration -- The creation of state responsibility in the new world -- International responsibility as German philosophy -- State responsibility as world order -- Epilogue : from state responsibility to the responsibility of states.
BIBINDX
Keywords: Government liability (International law) -- History; Government liability